PENGGUNAAN ASAS SEDERHANA DALAM PENDAFTARAN TANAH ELEKTRONIK (STUDI KASUS KANTOR PERTANAHAN KOTA TANGERANG): Use of Simple Principle Electronic Land Registration (Case Study of Tangerang City Land Office) - Hermanto, Suluh Annastasya; Indiraharti, Novina Sri (Faculty of Law, Universitas Trisakti, 2024)
Electronic land registration begins with the government's innovation to create a simple principle in land registration services, with the problem of whether the simple principle of electronic land registration at the Tangerang City Land Office is in accordance with the applicable provisions, and how to resolve the law if there are legal constraints in electronic land registration at the Tangerang City Land Office. The methodology of research used in this journal is normative research with The conclusion of this research is a simple principle in land registration regulated in article 2 of Government Regulation No. 24 of 1997 aims to make the procedure of land registration easier to understand and does not take long, however its implementation has not been fulfilled and in its implementation there are also legal obstacles, namely that there is often a data mismatch with those in the field which has an impact on legal